ANALISIS UNSUR ITIKAD BAIK PADA MEREK NAMA ORANG TERKENAL DALAM PASAL 21 UNDANG – UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS (STUDI KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 48/PDT.SUS/MEREK/2018/PN NIAGA JKT.PST) - Iqbal Akbar Mandiri; Simona Bustani (Fakultas Hukum Universitas Tarumanagara, 2020)
Based on the related trademark dispute that occurred in Indonesia and which the author will use as research material is the Supreme Court's Decision Number: 48 / Pdt.Sus / Trademark / 2018 / PN.Niaga.Jkt.Pst which checks and decides on the BENSU brand dispute. The Plaintiff's trademark is none other than the impact of public attention on the Plaintiff with the word BENSU attached to the Trademark, and therefore the Plaintiff has objected to the Plaintiff's registered trademark thereby making public opinion